The Importance of Lifeboat Winch Maintenance for the Safety of Crew and Passengers on the KM Sultan Hasanuddin Training Ship - Winarno; Rahman, Fajrur; Muhlisin; Girikallo, Adrianus; Kasim, Setiawan; Noegraha, Andi Dirga (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2026)
The main objective of this study is to evaluate the effectiveness of the lifeboat winch maintenance program and identify internal and external factors that affect its implementation. The research method used a qualitative descriptive approach through observation of the physical condition of the equipment, interviews with the crew, and review of logbooks. The results of the study show that the lifeboat winch maintenance program on KM Sultan Hasanuddin is not yet effective. The condition of the equipment shows degradation, such as rust on the wire rope and blurred nameplates, while the Planned Maintenance System (PMS) documentation is not available. Safety drills are conducted, but passenger involvement is not guaranteed, thereby reducing collective preparedness. Internal factors that influence this include the competence of the crew, the availability of spare parts, the consistency of the maintenance schedule, and the safety culture. External factors include the corrosive marine environment, ship operator policies, budget constraints, and weak external supervision. The implications of these findings emphasize the need for the implementation of a documented PMS, consistent preventive maintenance, and integrated drills involving all parties on board. For maritime educational institutions, this research also serves as a basis for the development of practical learning modules on lifeboat winch maintenance to support the formation of a safety culture from an early stage.